A Virtual Wellness and Learning Communities Program for Medical Students during the COVID-19 Pandemic. Issue 12 (December 2021) - Ahlers, Carolyn G.; Lawson, Victoria; Lee, Jaclyn; March, Cooper; Schultz, Jacob; Anderson, Katherine; Neeley, Maya; Fleming, Amy E.; Drolet, Brian C.
Abstract: Objectives: Numerous studies have demonstrated the high risk for burnout and mental illness in medical students. Because of the coronavirus disease 2019 (COVID-19) pandemic, our medical school transitioned to an all-virtual learning environment from March to June 2020, which raised concerns among student leaders and administrators, as reduced interpersonal attachments have known associations with decreased mental health. In an effort to facilitate student well-being during the pandemic, the Virtual Wellness and Learning Communities (VWLC) program was established. VWLC consisted of hour-long events that offered students the opportunity to engage with their peers online. Methods: More than 20 events and workshops were conducted from March to June 2020, including trivia nights, song and guitar performances, sketching, video editing tutorials, chess lessons, yoga, and personal investing tips. An institutional review board–approved survey to assess the efficacy of the VWLC program was sent to medical student participants and nonparticipants. Results: The overall response rate of this study was 43% (53/123). The response rate for students who attended a VWLC event was 51% (33/65), and the response rate for students who did not attend a VWLC event was 34% (20/58). Of all of the respondents, 85% (45/53) reported a decreased sense of connectivity with peers because of the pandemic, and 40% (21/53) reported a decrease in their sense of wellness. After attending a VWLC event, 79% (26/33) reported an increased sense of peer connectivity, 61% (20/33) reported improved wellness, and 55% (18/33) believed that these events should continue postpandemic to supplement in-person programming. Those who did not attend a virtual event stated that the main barriers to attending were unfamiliarity with attendees and screen fatigue. Conclusions: The COVID-19 pandemic has worsened medical student well-being and sense of community. VWLC programming may be an effective strategy for promoting medical student wellness and community while social distancing during the COVID-19 pandemic. To our knowledge, this is the first virtual wellness program for promotion of medical student mental health during the COVID-19 pandemic to be described in the literature. Abstract : Because of the coronavirus disease 2019 pandemic, the authors' medical school transitioned to an all-virtual learning environment from March to June 2020, which raised concerns among student leaders and administrators as reduced interpersonal attachments have known associations with decreased mental health. In an effort to facilitate student well-being during the pandemic, the Virtual Wellness and Learning Communities program was established. The authors evaluate the effect of this Virtual Wellness and Learning Communities program on medical student sense of wellness and community during the pandemic.